Qualidade de sementes de tabaco durante o processo de pelotização e armazenamento - Caldeira, Carla Massimo (2016)
The pelletizing process may affect the quality of seeds during sowing. In order to evaluate the effect of this process on seed quality it was used seeds from three tobacco cultivars, 'CSC 467' and 'CSC 07' collected in different processing and pelletizing process stages: 1) non processed nude seeds; 2) processed nude seeds; 3) pelletized seeds; 4) pelletized and colored seeds. For the evaluation of seed quality in these different stages it was performed the following tests: Germination, First Count of Germination, Germination Speed Index, Initial and Final Stand (Emergence) and Emergence Speed Index. Posteriorly, seeds were stored for six and twelve months and their quality was evaluated by the same tests and determinations. The evaluated pelletizing process does not influence final germination of the tobacco seeds, but delays the germination process. Tobacco seeds from cultivars 'CSC 467' and 'CSC 07' maintain their quality during the 12 months of storage in cold chamber with temperature of 10oC and relative humidity of 50%.